297. Lactobacillus: Friend or Foe. (31st December 2020) - Nwanyanwu, Chiemeziem; Shobayo, Anuoluwapo; Ghitan, Monica; Chapnick, Edward; Kuhn-Basti, Margaret; Lin, Yu Shia; Simon, Samuel; Li, Rosanna
Abstract: Background: Lactobacillus are low virulence commensal organisms which are commonly found in the human oral cavity, gastrointestinal and genitourinary tracts. Although Lactobacillus bacteremia (LB) is rare, evidence aggregating from case reports has implicated LB in several medical conditions. As such, there is reason to suggest that the presence of these organisms in blood cultures may not be due to spurious contamination, but rather, indicative of clinically meaningful events capable of inducing serious illnesses. The purpose of this study is to characterize the risk factors, clinical significance and outcomes of patients with LB. Methods: We retrospectively reviewed the medical records of patients presenting to a large urban teaching hospital between January 1, 2017 and December 31, 2018, who were found to have LB. Identified individuals were grouped into two mutually exclusive case categories: true LB cases or non-true cases (i.e., contamination). Individuals with ≥1 positive blood and were started on appropriate antibiotics were considered true cases. Those with positive cultures not started on appropriate antibiotics were considered contaminants. Results: A total of 14 patients were identified during our study period, with majority considered true LB cases [71.4%; n = 10]. These 14 individuals were mostly males [64.2%; n = 9] and reported no use of Lactobacilli probiotics [78.6%; n = 11] or antacids [57.1%; n = 8]. On average, true LB cases were older (mean [SD]): 80.1 [±10.9]vs. 54.0 [±19.1] years) and required longer hospitalization (38.5 [(±27.6] vs. 8.0 [(±6.2] days) compared to non-LB cases, respectively. Among the 10 true LB cases, the suspected source of infection included gastrointestinal system [50%; n = 5], infective endocarditis [10%; n = 1], genitourinary system [10%; n = 1]; and could not be determined in 3 [30%] cases. Concurrent infection with candida and gastrointestinal microbes were noted in four (40%) of the true LB cases, respectively. Overall, five deaths were observed, with 4 [80%] occurring in true LB cases and one in a non-LB case. Conclusion: LB should not be dismissed as contaminants particularly in at-risk patients for LB, such as the elderly or immunocompromised individuals. Disclosures: All Authors : No reported disclosures